(untitled) (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Work stress is a common issue faced by healthcare workers, particularly nurses. It arises when there is an imbalance between an individual’s capabilities and the demands of the work environment; the greater this mismatch, the higher the level of stress experienced. Various factors have been identified as contributors to work stress, including workload, work shifts, lighting conditions, and age. This study aimed to examine the relationship between workload, work shifts, lighting intensity, and age with work stress among psychiatric nurses at RSUD Madani in Central Sulawesi Province. A quantitative analytic method with a cross-sectional design was employed. The study involved total sampling, with 54 nurses participating as respondents. Data were collected using structured questionnaires based on Likert and Guttman scales. The results indicated significant associations between workload (p = 0.001) and work shifts (p = 0.019) with work stress. However, no significant relationships were found between lighting intensity (p = 0.791) or age (p = 0.181) and work stress. These findings suggest that workload and shift schedules are key factors influencing work stress among nurses in inpatient units. Therefore, it is recommended that RSUD Madani’s management adjust nurses’ workloads and improve shift scheduling in order to reduce work stress effectively.